1991
DOI: 10.1007/bf00014780
|View full text |Cite
|
Sign up to set email alerts
|

Growth of asparagus in a commercial peat mix containing vesicular-arbuscular mycorrhizal (VAM) fungi and the effects of applied phosphorus

Abstract: Commercially prepared, peat-based mycorrhizal inocula were studied for growth effects on asparagus grown under greenhouse and field (fumigated) conditions. The fungi tested were Glomus clarum (GC), G. intraradix (GI), G. monosporum (GM), G. versifomre (GVR) and G. vesiculiferum (GVS). GI significantly increased plant dry weight in the greenhouse and the field. Survival of mycorrhizal tissue-cultured transplants after 14 months in the field was increased by twofold over the control. In a second experiment aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In contrast, the AM beds in this study showed significantly increased yields without an associated increase in plant P concentration. Similar growth increases in the absence of P concentration effects were reported in sweetgum (Liquidambar styraciflua L.) (Schultz et al, 1979), and in asparagus using the same AM inoculum as we have used here (Pedersen et al, 1991). In a 1994 report, Volpin et al showed an AM-induced increase in isoflavonoid production in alfalfa (Medicago sativa L.) under very low levels of hyphal colonization in the root tissue.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, the AM beds in this study showed significantly increased yields without an associated increase in plant P concentration. Similar growth increases in the absence of P concentration effects were reported in sweetgum (Liquidambar styraciflua L.) (Schultz et al, 1979), and in asparagus using the same AM inoculum as we have used here (Pedersen et al, 1991). In a 1994 report, Volpin et al showed an AM-induced increase in isoflavonoid production in alfalfa (Medicago sativa L.) under very low levels of hyphal colonization in the root tissue.…”
Section: Discussionsupporting
confidence: 81%
“…The effects of peat-based AM inoculum have been investigated in soilless substrates commonly used in the production of many horticultural crops (Ponton et a!., 1990;Pedersen eta!., 1991). Mycori-Mix (Premier Peat Moss, Riviere-du Loup, Quebec, Canada), a commercial peat-based AM inoculum, has been tested on asparagus (Asparagus officina/is L.) (Pedersen et a!., 1991) and leek (Allium porrum; syn. A. ampeloprasum L. Porrum group) (Caron and Parent, 1988), and shown to enhance AM colonization and increase yield.…”
mentioning
confidence: 99%
“…All plots were treated with N (as NH 4 NO 3 ) at 56 kg/ha and K (as K 2 SO 4 ) at 50 kg/ha at planting and in spring of 2000 and 2001. Phosphorus was not applied because soil tests revealed sufficient P and because high P conditions inhibit VAM colonization (30). Weeds were removed by hand in 1999.…”
Section: Source Dfmentioning
confidence: 99%
“…The benefit from mycorrhizal colonization may be related to the amount of colonization established early in the seedling stage of plant growth (Boswell et al, 1998;Pedersen et al, 1991). However, some attempts to colonize roots growing in soilless media have resulted in low levels of colonization (Biermann and Linderman, 1983a;Johnson and Hummel, 1986;Nemec, 1987;Pedersen et al, 1991). There are, therefore, few documented examples of the successful use of VAM fungi in horticultural production, particularly in floriculture (Chang, 1994;Miller et al, 1986).…”
mentioning
confidence: 99%